Safe Food Production Regimes and Potentiality of Integrated Multi-Level Food Certification System in Nepal - Pandit, J.; Karki, Y. K.; Gauchan, D.; Paudel, B. (Journal of Agriculture and Environment, 2021)
There is continuum of agricultural production systems between highly agrochemical intensive farming and pure organic system. The current certification system in Nepal involve two levels – organic and good agriculture practice (GAP). Other middle-way alternatives for safe food like traditional and pesticide-free systems have not been considered for certification. This paper analyses various safe-food production regimes and explore potential for integrated multi-label food-safety certification system. Taking four typologies with varied levels of food safety i.e. traditional, good agriculture practice (GAP), pesticide-free and organic products as alternatives to input-intensive production systems, this paper concludes that the integrated multi-label food safety certification system would provide choice for consumers to make price and food-safety trade-off. Labelled safer food alternatives would enable consumers to choose and pay for their safe-food need and increase consumption of safer food contributing to sustainable growth of agriculture sector